Personel Management in Fostering The Learning Discipline of Student at SMK Al-Asy’ariyah - Saja, Windi (IAIN Syekh Nurjati Cirebon, 2021)
PERSONNEL MANAGEMENT IN FOSTERING THE LEARNING DISCIPLINE OF STUDENT AT SMK Al-ASY’ARIYAH KALISARI LOSARI CIREBON ABSTRACKPersonnel management is an effort to manage teaching and education personnel with the aim of obtaining and improving the quality of competent education personnel, so that they can carry out their role as a driving force for educational components such as students optimally according to educational goals. This study aims to determine (planning, implementing and evaluating) personnel management and role of personnel in fostering the tearning fiscipline of student in SMK Al-Asy’ariyah Kalisari Losari Cirebon. The research methodology used is descriptive qualitative method, with data collection using interview techniques, observation and documentation, then analyzed with data analysis techniques such as data collection, reduction, presentation data and drawing conclusions. The results of the study show that personnel management activities have been carried out, although not optimally, because there are activities that have not been carried out, and the role of personnel in fostering student learning discipline is carried out with various efforts such as socializing the rules of learning discipline, giving sanctions,rewards and examples by educational personnel. It can be concluded that less than optimally personnel management has an impact on the quality of its role in foresting student learning discipline that is not running optimally, because students still violate the rules of learning discipline. Keywords : Personnel Management, Discipline learning, Student.MANAJEMEN PERSONALIA DALAM MENUMBUHKAN KEDISIPLINAN BELAJAR PESERTA DIDIK DI SMK AL-ASY’ARIYAH KALISARI LOSARI CIREBON ABSTRAK Manajemen personalia merupakan upaya pengelolaan tenaga pendidik dan kependidikan bertujuan untuk mendapatkan dan meningkatkan kualitas personalia pendidikan yang berkompeten, sehingga dapat menjalankan perannya sebagai penggerak komponen pendidikan seperti peserta didik secara optimal. Penelitian ini bertujuan untuk mengetahui (perencanaan, pelaksanaan dan evaluasi) manajemen personalia serta peran personalia dalam menumbuhkan kedisiplinan belajar peserta didik di SMK Al-Asy’ariyah Kalisari Losari Cirebon. Metodologi penelitian yang digunakan yaitu kualitatif deskriptif, dengan pengumpulan data menggunakan teknik wawancara, observasi dan dokumentasi, kemudian dianalisis dengan teknik analisis data seperti pengumpulan data, reduksi, penyajian data dan penarikan kesimpulan. Hasil penelitian bahwa kegiatan manajemen personalia sudah dilakukan, meskipun belum optimal, karena terdapat kegiatan yang belum dijalankan, serta peran personalia dalam menumbuhkan kedisiplinan belajar peserta didik dilakukan dengan berbagai upaya seperti sosialisasi aturan kedisiplinan belajar, pemberian sanksi, penghargaan sampai tauladan oleh personalia pendidikan. Maka dapat disimpulkan bahwa manajemen personalia yang kurang optimal berdampak pada kualitas perannya dalam menumbuhkan kedisiplinan belajar peserta didik yang kurang berjalan optimal, karena peserta didik masih melanggar aturan kedisiplinan belajar. Kata Kunci : Manajemen Personalia, Kedisiplinan Belajar, Peserta didik.